Pembelajaran Matematika dengan Media Obrolan Kelompok Multi-Arah sebagai Alternatif Kelas Jarak Jauh - Ratih Ayu Apsari; Sripatmi Sripatmi; Sariyasa Sariyasa; Mohammad Archi Maulyda; Nilza Humaira Salsabila (Jurnal Elemen, 2020)
The sudden change caused by the global pandemics of COVID-19 leads to the classroom transformation from classical face-to-face meetings into virtual. The development of technology enables classroom variation by providing various applications that can be employed to facilitate learning activities. Nonetheless, not all situations suitable to use advanced technology during distance learning. Some students are living in remote areas with limited internet connection. This study aims to offer an alternative if most of the students were having difficulties with the internet and minimum devices to download heavy applications. The alternative is by using a chat group with an emphasis on the students’ interaction during the lesson. This descriptive study was conducted at a university in Mataram, Indonesia. The subject was 17 students in the Mathematics Education Study Program who follow the course of Abstract Algebra. The data were gathered from students’ observation during the lessons and students’ written work in the middle semester test. The data were analyzed by using descriptive qualitative method. From the analysis, it was found that the students’ activity during distance learning was 83.5%. Furthermore, 88.23% of students achieved the minimum score for the middle semester test (more than 56). The study showed that mathematics teaching and learning could be done with a secure and straightforward access application to gain good results.